Foreign experiences in developing students’ independent study skills - Aziza, Rahimjonova (The Lingua Spectrum, 2025)
This article analyzes the experiences of the United Kingdom, Finland, Singapore, Australia, the United States, and Uzbekistan in developing students’ independent study skills. International practices demonstrate that independent learning skills are among the most essential competencies required of students in modern education systems. The article highlights the role of theories such as self-regulated learning and self-determination theory in fostering independent study, as well as the use of digital technologies in organizing students’ independent learning activities.